Qualitative and quantitative analysis of the relevance, clarity, and comprehensibility of the Scale of Quality of Diet (ESQUADA) - Souza Santos, Thanise Sabrina; de Morais Sato, Priscila; Regina Carriero, Maria; Perucchi Lopes, Clarice; Emanuelly Segura, Iris; Baeza Scagliusi, Fernanda; Altenburg de Assis, Marie Alice; Slater Villar, Betzabeth (Archivos Latinoamericanos de Nutrición (ALAN), 2019)
The study of the diet quality should include not just the nutritional adequacy but also incorporate the multidimensional understanding and the current dietary recommendations. This study aimed to evaluate the relevance, clarity, and comprehensibility of the Scale of Quality of Diet (ESQUADA). Nutritionists’ perspectives about the relevance and clarity of the items were evaluated through focus groups between November and December 2016. An exploratory content analysis investigated the themes that emerged from the focus groups, which were organized in a structured codebook. Two reviewers applied it to the data. Inter-rater reliability was analyzed by the kappa coefficient. The coding was analyzed using the frequencies and central aspects of the sub-themes. Laypersons’ comprehension of the items was evaluated using a question regarding whether they understood each item in online questionnaire in February 2018. Descriptive statistics investigated the comprehensibility of each item. The reviewers presented adequate reliability on coding the data. Three themes emerged from the data considering the nutritionists’ suggestions. The theme Item relevance indicated that the items assessed diet quality while considering sociocultural influences. However, the nutritionists suggested attention was needed to how some items were expressed and their response options. Of relevance, the themes Item clarity and Clarity of alternatives primarily encompassed discussions regarding item text (44%) and discrimination of alternatives (24%). The study of the comprehensibility indicated that all items were readily understood. These results support the relevance of the ESQUADA for evaluating quality of diet as well the comprehensibility of all the items by individuals uneducated in public health. El estudio de la calidad de la dieta debe incluir la adecuación nutricional además sus dimensiones y las recomendaciones dietéticas actuales. Este estudio evaluó la relevancia, claridad y comprensibilidad de la Escala de Calidad de la Dieta (ESQUADA). Las perspectivas de los nutricionistas sobre la relevancia y claridad de los ítems se evaluaron en grupos focales entre noviembre y diciembre de 2016. Un análisis de contenido exploratorio investigó los temas que surgieron de los grupos. Estos temas fueron ordenados en un libro de códigos estructurado. Dos revisores lo aplicaron a los datos. La fiabilidad inter-evaluadores fue analizada por el coeficiente kappa. La codificación se analizó utilizando las frecuencias y aspectos centrales de los subtemas. La comprensión de los ítems por personas sin conocimientos de nutrición se evaluó mediante una pregunta sobre el entendimiento de cada ítem en uno cuestionario online in febrero de 2018. Las estadísticas descriptivas investigaron la comprensibilidad de cada ítem. Los revisores presentaron adecuada fiabilidad en la codificación de los datos. Tres temas surgieron de los datos. El tema Relevancia del ítem indicó que los ítems evaluaron la calidad de la dieta mientras consideraban las influencias socioculturales. Sin embargo, los nutricionistas sugirieron la necesidad de atención en el texto de algunos ítems y sus opciones de respuesta. Los temas Claridad del ítem y Claridad de las opciones abarcaron principalmente las discusiones sobre el texto del ítem (44%) y la discriminación de las opciones (24%). El estudio de la comprensibilidad indicó que todos los ítems se entendían fácilmente. Estos resultados apoyan la relevancia de ESQUADA para evaluar la calidad de la dieta y la comprensión de todos los ítems por personas sin conocimientos de nutrición.